Characteristics of dysphagia among different lesion sites of stroke: A retrospective study - Qiao, Jia; Wu, Zhi-min; Ye, Qiu-ping; Dai, Meng; Dai, Yong; He, Zi-tong; Dou, Zu-lin (Frontiers in Neuroscience, 2022)
Objective: To compare the characteristics of dysphagia among different lesion sites after stroke, and explore the possible factors that are relevant to penetration and aspiration. Method: Data on patients with post-stroke dysphagia were collected. Major measures of Videofluoroscopic Swallowing Study included pharyngeal transit duration (PTD), pharyngeal response duration (PRD), soft palate elevation duration (SED), stage transition duration (STD), hyoid bone anterior-horizontal displacement (HAD), hyoid bone superior-horizontal displacement (HSD), upper esophageal sphincter opening (UESO), Pharyngeal Residual Grade (PRG), Penetration Aspiration Scale (PAS). The patients included were divided into supratentorial (deep or lobar intracerebral) and infratentorial stroke groups. The Kruskal-Wallis test, Spearman correlation analysis and multivariate logistic regression analyses were used to test the difference and the correlation between the measures. Time-to-event end points (oral feeding) were analyzed by Kaplan-Meier method. Result: A total of 75 patients were included. A significant difference was demonstrated in PTD, PRD, SED, STD, HAD, HSD, UESO, PAS, PRG and the time-to-oral feeding between supratentorial and infratentorial stroke groups (p<0.05). In lobar intracerebral group, the PRG score was significantly higher (p<0.05) and HSD was significantly shorter (p<0.01) than that in deep intracerebral stroke subgroup. There was statistical relevance between PAS and PTD, PRG, HAD, and UESO, in which HAD and PRG were risk factors of penetration and aspiration (p<0.05). Conclusion: Infratentorial may lead to worse swallowing function as compared to supratentorial stroke, and lobar intracerebral may be worse than deep intracerebral stroke. Suitable preventive measures may be considered for patients with higher PRG scores and shorter HSD.